Profiling physiotherapy students’ interactions patterns in history taking - Harni Kartika-Ningsih; Faizah Abdullah Djawas (Indonesian Journal of Applied Linguistics, 2022)
In physiotherapy education, history taking – in which a physiotherapist interacts with a patient to determine a prognosis – requires a set of communication skills which can be challenging for most student physiotherapists. One way to better understand the struggle that the students face is to examine the language and function of the interactions they use. This paper aims to investigate the way students perform their communication skills in history taking role-play. This study employed a qualitative discourse analytic method following the interpersonal discourse of NEGOTIATION, genre and register frameworks from the systemic functional linguistics. The data were obtained from a recorded students‘ role-play for their final assignments in a physiotherapy class. These data were then analysed by following the discourse analytic frameworks to map the structures and function of their interactions. The findings reveal that the students structure history taking stages similarly, while the length of exchange structures they build to gather information show differences in which skilled students tended to be more extensive in the interactions. The findings suggest that making explicit of the stages and move options may provide better awareness of the available choices the students can have in the history taking interactions.